Advances in ex vivo expansion of hematopoietic stem and progenitor cells for clinical applications - Branco, André; Rayabaram, Janakiram; Miranda, Cláudia C.; Fernandes-Platzgummer, Ana; Fernandes, Tiago G.; Sajja, Suchitra; da Silva, Cláudia L.; Vemuri, Mohan C. (Frontiers in Bioengineering and Biotechnology, 2024)
As caretakers of the hematopoietic system, hematopoietic stem cells assure a lifelong supply of differentiated populations that are responsible for critical bodily functions, including oxygen transport, immunological protection and coagulation. Due to the far-reaching influence of the hematopoietic system, hematological disorders typically have a significant impact on the lives of individuals, even becoming fatal. Hematopoietic cell transplantation was the first effective therapeutic avenue to treat such hematological diseases. Since then, key use and manipulation of hematopoietic stem cells for treatments has been aspired to fully take advantage of such an important cell population. Limited knowledge on hematopoietic stem cell behavior has motivated in-depth research into their biology. Efforts were able to uncover their native environment and characteristics during development and adult stages. Several signaling pathways at a cellular level have been mapped, providing insight into their machinery. Important dynamics of hematopoietic stem cell maintenance were begun to be understood with improved comprehension of their metabolism and progressive aging. These advances have provided a solid platform for the development of innovative strategies for the manipulation of hematopoietic stem cells. Specifically, expansion of the hematopoietic stem cell pool has triggered immense interest, gaining momentum. A wide range of approaches have sprouted, leading to a variety of expansion systems, from simpler small moleculebased strategies to complex biomimetic scaffolds. The recent approval of Omisirge, the first expanded hematopoietic stem and progenitor cell product, whose expansion platform is one of the earliest, is predictive of further successes that might arise soon. In order to guarantee the quality of these ex vivo manipulated cells, robust assays that measure cell function or potency need to be developed. Whether targeting hematopoietic engraftment, immunological differentiation potential or malignancy clearance, hematopoietic stem cells and their derivatives need efficient scaling of their therapeutic potency. In this review, we comprehensively view hematopoietic stem cells as therapeutic assets, going from fundamental to translational.